Analysis of Business Development Strategies Using Smart Business Map at Bumdesa Tourist Business Unit Wa Hyang Tarumajaya - Ivana Nafliyon; Aldi Akbar (Return : Study of Management, Economic and Bussines, 2023)
The charm of Indonesian tourism is known to have unique characteristics and the development of tourism in villages is considered more strategic and provides many benefits, especially in the economic aspect. But there are still many tourist attractions that have not maximized it so that the number of tourists is low, for example in Tarumajaya Village. This research aims to be a new business strategy for the management of the Tarumajaya Village Tourism Business Unit based on the Smart Business Map which is reviewed from the results of the Playing Field, Marker Landscape, and Operational Profitability analysis. The research method used is descriptive qualitative with an inductive approach to data analysis. Primary data was obtained through interviews with the Director and Manager of the tourism business unit BUMDesa Wa Hyang Tarumajaya. The results of the study indicate that the tourism business unit BUMDesa Wa Hyang Tarumajaya experiences difficulties in developing modern tourism. The strategy includes developing a playing field to expand tourists and achieve more positive business development, Market Landscape to increase visitor volume and build bonds with tourists, and Operational Profitability to increase revenue, manage expenses with efficiency, use core resources optimally, and develop skilled and competent teams.